Behavioral Implications of the Covid-19 Process for Autism Spectrum Disorder, and Individuals' Comprehension of and Reactions to the Pandemic Conditions - Mutluer, Tuba; Doenyas, Ceymi; Aslan Genc, Herdem (Frontiers in Psychiatry, 2020)
During disasters and pandemics, vulnerable populations such as patients with mental conditions are known to be overly influenced. Yet, not much is known about how the individuals with autism spectrum disorder (ASD), one of the most common neurodevelopmental conditions globally with a prevalence of 1%, are affected from health-related disasters, especially the current Covid-19 pandemic. Therefore, we conducted an investigation of how individuals with ASD responded to Covid-19 in terms of comprehension and adherence to implemented measures; changes in their behavioral problems; and how their caregivers’ anxiety levels relate with these behavioral changes. Our sample consisted of 87 individuals with ASD (15 girls; ages ranged between 3-29, with an average of 13.96 + 6.1). The majority of our sample had problems understanding what Covid-19 is and the measures it requires. They also had challenges in implementing social distance and hygiene-related regulations of the pandemic. The majority stopped receiving special education during this period. We observed a Covid-19-related clinical presentation that resembled PTSD in individuals with ASD in terms of increased stereotypies, aggression, hypersensitivity, behavioral problems, and sleep and appetite alterations. All subscales of Aberrant Behavior Checklist (ABC) differed significantly between before and after the pandemic conditions. The number of hours the children slept significantly decreased from before to during Covid-19. The anxiety levels of caregivers were high and correlated with the current behavioral problem levels of their children, but not with the level of their behavioral problems before the pandemic. The difference in ABC total score and specifically the lethargy/social withdrawal subscale score predicted parents’ anxiety score. Our results suggest that the Covid-19 period inflicts specific challenges to individuals with ASD and their caregivers, underlining the need for targeted, distance special education interventions and other support services for this population.